Calculating the Dynamic Impedances of Foundations and their Effect on the Seismic Response of Structures: Analytical and Numerical Study - Boulkhiout, Radhwane; Messast, Salah (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study evaluates the movement of a frame built on soft soil under seismic excitation taking into account soil-structure interaction. First, the study was evaluated using the finite element method, then, by using a substructure method which modelled the soil using springs and dampers in a linear and nonlinear study. Rheological models were determined using impedance functions, calculated using a numerical program CONAN.
Keywords: soil-structure interaction; Finite Element Method (FEM); substructure method; impedance functions; CONAN; equivalent static method; soil densification; interakcja gleba-struktura; metoda elementów skończonych (MES); równoważna metoda statyczna; zagęszczanie gleby